Предмет: Алгебра,
автор: dipraiel01
упростить выражение, и обчислите
Приложения:
Ответы
Автор ответа:
0
Ответ:
0,16
Объяснение:
4m(3+5m) -(m+1)(m-2)=12m + 20m² -(m²+m-2m-2)=
=12m + 20m² - m²+m+2=19m² +13m +2
при m=-0,2 19·(-0,2)² + 13·(-0,2) +2=19·0,04 - 2,6 +2=0,76 - 0,6=0,16
Похожие вопросы
Предмет: Информатика,
автор: lefinol
Предмет: Математика,
автор: skorinaanastasiya220
Предмет: Другие предметы,
автор: lokogg3749
Предмет: Математика,
автор: dana47173
Предмет: Английский язык,
автор: majorovaekaterina86